... Rethinking State Theory Gramsci and Contemporary - Dharma Prasetyo, Dwi; Sinaga, Jona Bungaran Basuki; Soleh, Mohamad; Haekal, Muhammad (International Journal on Social Science, Economics and Art, 2025)
One of the most significant aspects of Antonio Gramsci’s social theory is his analysis of political strategy, particularly his distinction between "war of maneuver" and "war of position." Gramsci argued that the classical model of revolution through military insurrection (war of maneuver) has been replaced by a much longer and more complex cultural struggle within advanced capitalism (war of position). Despite the importance of these concepts for contemporary Marxism, they have received relatively little attention. These terms have a history rooted in both military theory and Marxism, predating Gramsci’s prison notebooks, as reflected in the writings of Engels, Lenin, and Trotsky, which offer different perspectives on political strategy.